Teori Belajar Sosial dalam Perspektif Hadits-Hadits Akidah Akhlak - Arifin, Zainal; Kattani, Abdul Hayyie Al; Alim, Akhmad; Tamam, Abas Mansur; Rahman, Imas Kania (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
Islam is the perfect religion, the Messenger of Allah is the most noble Messenger, so all of his teachings and his entire life describe this glory, including in carrying out his duties as an Apostle, reciting the Qur'an, teaching it and guiding his people to purify their souls, so that all learning theories are true. has been portrayed and exemplified by the Prophet SAW including social learning theory. Because in this short article several hadiths and histories are mentioned as examples of the form of social learning theory even though it is limited to hadith hadiths in the chapter on faith and morals, even though in fact there are many examples of social learning in theory in the sunnah of the Prophet SAW with his companions who always get outpourings knowledge. Social learning theory can be seen from the observations and observations, retention, reproduction and motivation. If the above is realized, then the social learning theory materializes. Hopefully, from the examples of the Prophet's hadiths, social learning theory can be additional knowledge and belief in the perfection of Islamic teachings.